Strategies to enhance quality data input requirements of life cycle cost (LCC) - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (Kulliyyah of Architecture and Environmental Design, IIUM, 2013)
Commentators pointed out that one of the major hurdles of implementing LCC analysis in the Malaysian construction industry is lack of current and reliable data. In addition, most of LCC researchers and estimators in the Malaysian construction industry considerably focused on the LCC conversion process but very little emphasis is given on the availability, accessibility, currency and reliability of data as inputs into the process of producing reliable LCC outputs. This paper reports part of a three-year programme of research to enhance quality of LCC outputs through the enhancement of quality data input requirements. The objective of this paper is to present on the development, evaluation and validation of the most appropriate strategies to improve the availability, accessibility, currency and reliability of data as inputs into the process of producing reliable LCC analysis in the Malaysian construction industry. Looking at the results of the most appropriate strategies which have been prioritized, there is an overwhelming requirement for a clear procedure or comprehensive guideline to be prepared on the acquisition of cost data inputs to enhance quality data input requirements of LCC. This clear procedure can be best translated in the form of model, framework or protocol to be developed so that a step by step methodological approach can be exacted to make the data available, accessible, current and reliable in facilitating the clients, estimators and researchers to better calculate LCC leading to better outputs.